2019
DOI: 10.29399/npa.23444
|View full text |Cite
|
Sign up to set email alerts
|

Frailty in Patients with Parkinson’s Disease: Associations with Disability and Timed Up and Go

Abstract: Introduction: Aim of this study was identify the prevalence of frailty in patients with idiopathic Parkinson’s disease (PD), to describe the relationship between severity of the disease and frailty, and to evaluate if timed up and go (TUG) is an eligible test for determination of frailty in idiopathic PD patients. Methods: We conducted a cross-sectional study which included 66 patients, aged 60 and over in a tertiary hospital. Frailty was assessed by the Fried Frailty I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Higher daily dose of levodopa carbidopa has been also shown to be associated with frailty [25] . Findings reported in a conference abstract found that frailty was positively associated with levodopa dose ≥400 mg (OR 26.78; 95% CI 1.34–535.45) [20] .…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Higher daily dose of levodopa carbidopa has been also shown to be associated with frailty [25] . Findings reported in a conference abstract found that frailty was positively associated with levodopa dose ≥400 mg (OR 26.78; 95% CI 1.34–535.45) [20] .…”
Section: Resultsmentioning
confidence: 97%
“…Fifteen studies employed the frailty phenotype method [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] and 9 studies employed the clinical frailty scale [13] , [14] , [15] , [31] , [32] , [33] , [34] , [35] , [36] . Four studies employed the frailty index, or cumulative deficit model [19] , [27] , [37] , [38] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations